2004
DOI: 10.1007/s10384-003-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Eyeglass-free 3-D Display on the Human Visual System

Abstract: The effect on the human visual system of 3-D viewing of 3-D CG images depends on both the duration of the viewing and the apparent distance between the viewer and the virtual objects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…These problems occur only for short viewing distances in the range of 31.1-53.6 cm in a volumetric display [49] because of the depth of field of the human eye [56]. The results of this study are in good agreement with those obtained by Alhaag and Ramadan [57], Ukai and Howarth [58], Suzuki et al [59], and Fujikado [60]. In addition, it was explained that a wide field of view could cause more cyber sickness [61][62][63][64].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These problems occur only for short viewing distances in the range of 31.1-53.6 cm in a volumetric display [49] because of the depth of field of the human eye [56]. The results of this study are in good agreement with those obtained by Alhaag and Ramadan [57], Ukai and Howarth [58], Suzuki et al [59], and Fujikado [60]. In addition, it was explained that a wide field of view could cause more cyber sickness [61][62][63][64].…”
Section: Discussionsupporting
confidence: 82%
“…Ukai and Howarththe [58], Suzuki et al [59], and Fujikado [60] showed that the reason of conflict between the accommodation and vergence in 3D displays, which results in visual fatigue, is accommodation that should respond to the screen position but disparity in the two images for both the vergence stimulus of the eyes varies over time. These problems occur only for short viewing distances in the range of 31.1-53.6 cm in a volumetric display [49] because of the depth of field of the human eye [56].…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the 3-D viewing was 30 min, while that of the 2-D viewing was 90 min, and we selected these times because our earlier data had suggested that 3-D viewing had stronger effects on the accommodative step response than 2-D viewing. 11 To maintain the alertness and concentration of the subjects, we played an adventure movie for 2-D viewing.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental studies have demonstrated that the time of exposure to stereoscopic images has a negative impact on several oculomotor functions (see for instance [23,29,84,88]). In coherence, Rec.…”
Section: Contentmentioning
confidence: 99%